How Does House Demolition Affect Family Conspicuous Consumption? - Yuan, Wei; Gong, Shuying; Gao, Jun (Frontiers in Psychology, 2021)
Family conspicuous consumption behavior is affected by many factors. Existing literatures seldom focus on the impact of house demolition on family conspicuous consumption and its underlying mechanism. Based on the mental accounting theory and conservation of resources theory, this paper uses the micro-data of the 2011 China Household Finance Survey to empirically examine the relationship between house demolition and family conspicuous consumption. Robustness results suggest that house demolition positively affects household conspicuous consumption, which is not only reflected in the overall consumption level, but also in the level of average consumption. Further analysis find that household wealth and materialism value have a significant positive moderating effect on the relationship of main effect. In addition, in order to clarify the relationship between conspicuous consumption and luxury consumption, this paper finds that conspicuous consumption and luxury consumption are not completely equivalent through in-depth theoretical analysis and exploratory investigation. There are similarities in both consumption motivation and pattern, but with differences on consumer subject and object. The contribution of this research is to enrich the theory of decision-making in consumer behavior, which also has a certain significance to deepen the understanding of the relationship between conspicuous consumption and luxury consumption.